FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2016-2020 - Raditya, Raditya; Lukman, Hendro; Simina, Juni (Jurnal Paradigma Akuntansi, 2024)
This study aims to obtain empirical evidence about the influence that affects cash holding on consumer goods industrial sector companies listed on the Indonesian stock exchange in 2016-2020. This research is a quantitative research with purposive sampling method and produced as many as 123 companies. Furthermore, for hypothesis testing is done with multiple linear regression model. By using the SPSS ver 21 application. The results show that leverage does not have a positive effect on cash holding, on growth opportunity on cash holding, and net working capital has no effect on cash holding. Implication of this study is for investors who will invest in consumer goods industrial companies by looking at cash holdings, they may ignore leverage, growth opportunity, and net working capital.